Halichoerus Nilsson 1820 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Halichoerus Nilsson 1820 Halichoerus Nilsson 1820, Skand. Faun. Dagg. Djur., Vol. 1: 376. Type Species: Halichoerus griseus Nilsson 1820 Synonyms: Halychoerus Boitard 1842. Species and subspecies: 1 species with 2 subspecies: Species Halichoerus grypus (Fabricius 1791) Subspecies Halichoerus grypus subsp. grypus Fabricius 1791 Subspecies Halichoerus grypus subsp. macrorhynchus Hornschuch and Schilling 1851 Discussion: Mohr (1952) described successful mating in captivity between Pusa hispida and Halichoerus grypus . Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 596, DOI: 10.5281/zenodo.7316519